2006
DOI: 10.1128/jcm.00618-06
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method To Identify Source-Associated Phylogenetic Clustering Shows thatListeria monocytogenesIncludes Niche-Adapted Clonal Groups with Distinct Ecological Preferences

Abstract: While phylogenetic and cluster analyses are often used to define clonal groups within bacterial species, the identification of clonal groups that are associated with specific ecological niches or host species remains a challenge. We used Listeria monocytogenes, which causes invasive disease in humans and different animal species and which can be isolated from a number of environments including food, as a model organism to develop and implement a two-step statistical approach to the identification of phylogenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…While all lineage I and lineage III isolates characterized to date carry the A 2 GA 4 allele (28,29), only a few lineage II strains carry the A 2 GA 4 allele; the majority of lineage II strains carry the A 7 or A 6 allele. Collectively, the observations from these studies suggest that (i) disease-associated (i.e., lineage I and III) L. monocytogenes strains have evolved to carry an A 2 GA 4 allele that facilitates stable expression of the key virulence factor InlA, (ii) generalist strains (i.e., lineage II strains) have evolved a phase variation mechanism for inlA, allowing for selective silencing of inlA in environments where it may not be needed (e.g., food processing environments or foods), and (iii) some lineage II strains have acquired an A 2 GA 4 allele by point mutation or by horizontal gene transfer, suggesting that a subpopulation of lineage II strains have adapted to a disease-associated lifestyle, consistent with reports of lineage II isolates being identified from human and animal disease cases (30).…”
supporting
confidence: 60%
“…While all lineage I and lineage III isolates characterized to date carry the A 2 GA 4 allele (28,29), only a few lineage II strains carry the A 2 GA 4 allele; the majority of lineage II strains carry the A 7 or A 6 allele. Collectively, the observations from these studies suggest that (i) disease-associated (i.e., lineage I and III) L. monocytogenes strains have evolved to carry an A 2 GA 4 allele that facilitates stable expression of the key virulence factor InlA, (ii) generalist strains (i.e., lineage II strains) have evolved a phase variation mechanism for inlA, allowing for selective silencing of inlA in environments where it may not be needed (e.g., food processing environments or foods), and (iii) some lineage II strains have acquired an A 2 GA 4 allele by point mutation or by horizontal gene transfer, suggesting that a subpopulation of lineage II strains have adapted to a disease-associated lifestyle, consistent with reports of lineage II isolates being identified from human and animal disease cases (30).…”
supporting
confidence: 60%
“…Previous molecular epidemiology studies suggested that L. monocytogenes contains at least two distinct subpopulations that differ in virulence, including (i) epidemic clone strains, which have been associated with the majority of listeriosis outbreaks worldwide and which are overrepresented among sporadic cases in the United States, and (ii) strains carrying virulence-attenuating PMSC mutations in inlA, which are common in RTE foods but which are associated with human disease only on very rare occasions (12,14,25,26,27,35,43,44,46,47,48). Current L. monocytogenes risk assessments (8,42,50), which assume that an L. monocytogenes population with nonuniform variation in virulence is present in RTE foods, therefore likely underestimate the virulence of epidemic clone strains and overestimate the virulence of strains carrying a PMSC in inlA.…”
Section: Resultsmentioning
confidence: 99%
“…Previous molecular epidemiology studies suggest that L. monocytogenes genetic lineages and clonal groups within those lineages differ in their associations with human disease and isolation from foods (12,15,25,26,27,39,40,47,48,49). For example, three highly clonal L. monocytogenes strains within lineage I (termed epidemic clones I, Ia, and II) that belong to serotype 4b have been linked to the majority of listeriosis epidemics worldwide (9,17) and have frequently been isolated from sporadic listeriosis cases in the United States (12).…”
mentioning
confidence: 99%
“…Identification of 16S rDNA sequences associated with different source populations A distance matrix, generated by multiple alignments of 16S rDNA sequences for each isolate using phylogenetic analysis using parsimony (PAUP), was fed into SourceCluster to determine whether isolates from the same group (ICD, CCD, Healthy) clustered by sequence (Nightingale et al, 2006). In order to find specific branches in the phylogenetic tree, in which isolates from a specific group are more abundant or scarce than expected by chance, we used TreeStats.…”
Section: S Rdna Librariesmentioning
confidence: 99%